IMPLEMENTASI REWARD ASYIK DALAM MENINGKATKAN MOTIVASI BELAJAR ANAK DI PAUD NURUL ISLAM PANDEGLANG - Apriana Anggraini; Sri Watini (Jurnal Anak Bangsa, 2022)
This research is a qualitative research that aims to determine the increase in children's learning motivation in PAUD Nurul Islam Pandeglang Class B. With the pandemic, it turns out that it also has an impact on decreasing children's enthusiasm for learning at school. Therefore, the authors seek to find new innovations that can increase children's learning motivation at school. The method used by the author in an effort to increase student motivation at PAUD Nurul Islam Pandeglang is to use Reward ASYIK at the time of learning reflection. This ASYIK reward was first proposed by a Lecturer at Panca Sakti University Bekasi, Sri Watini, in 2016. This ASYIK reward is very easy to implement and the children are very happy to do it. This ASYIK reward is given to students when students can answer questions or can complete what is asked by the teacher. It starts with the teacher saying, “Say…,” then the child answers, “I can, I am great, I succeeded, yes”. This FUN reward is given with the aim of being able to motivate themselves that they are great. By using this ASYIK Reward, it can be seen that there is a change in the attitudes and learning motivation of children at PAUD Nurul Islam Pandeglang